1992
DOI: 10.1113/jphysiol.1992.sp019415
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of visceral and somatic inputs onto subnucleus reticularis dorsalis neurones in the rat medulla.

Abstract: SUMMARY1. In anaesthetized rats, recordings were made within the medullary subnucleus reticularis dorsalis (SRD) from neurones that exhibited convergence of nociceptive inputs from the entire surface of the body. Neurones with total nociceptive convergence responded to supramaximal percutaneous electrical stimuli (2 ms duration) with early and late peaks due to the activation of Ad and C fibres, respectively, no matter which part of the body was stimulated. Neurones with partial nociceptive convergence respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…Many neurons in the dorsal caudal medulla receive inputs from the spinal cord (Lima, 1990;Villanueva et al, 1991;Raboisson et al, 1996;Wang et al, 1999) and respond to noxious stimuli from wide areas of the body (Villanueva et al, 1988(Villanueva et al, , 1989Roy et al, 1992;Tsuruoka et al, 1997;Almeida et al, 1999). Similarly, the NTS receives inputs from neurons in the spinal cord (Menetrey and Basbaum, 1987;Mtui et al, 1993Mtui et al, , 1995Mifflin, 1994, 2000;Wang et al, 1999;Gamboa-Esteves et al, 2001), projects back to it via the solitariospinal tract (Loewy and Burton, 1978;Mtui et al, 1993Mtui et al, , 1995, and has been implicated in the processing of painful stimuli (Lewis et al, 1987;Aicher and Randich, 1990;Traub et al, 1996).…”
Section: Subnucleus Reticularis Dorsalis and Nucleus Tractus Solitariusmentioning
confidence: 97%
“…Many neurons in the dorsal caudal medulla receive inputs from the spinal cord (Lima, 1990;Villanueva et al, 1991;Raboisson et al, 1996;Wang et al, 1999) and respond to noxious stimuli from wide areas of the body (Villanueva et al, 1988(Villanueva et al, , 1989Roy et al, 1992;Tsuruoka et al, 1997;Almeida et al, 1999). Similarly, the NTS receives inputs from neurons in the spinal cord (Menetrey and Basbaum, 1987;Mtui et al, 1993Mtui et al, , 1995Mifflin, 1994, 2000;Wang et al, 1999;Gamboa-Esteves et al, 2001), projects back to it via the solitariospinal tract (Loewy and Burton, 1978;Mtui et al, 1993Mtui et al, , 1995, and has been implicated in the processing of painful stimuli (Lewis et al, 1987;Aicher and Randich, 1990;Traub et al, 1996).…”
Section: Subnucleus Reticularis Dorsalis and Nucleus Tractus Solitariusmentioning
confidence: 97%
“…Ammons et al (1985) showed that viscerocutaneous spinothalamic tract neurons project to the medial thalamus including the parafascicular and centrolateral nuclei and these nuclei receive input from the pronociceptive subnucleus reticularis dorsalis (Villanueva et al, 1998) as does the parabrachial nucleus (Bester et al, 1999). Both of these latter nuclei respond to visceral and cutaneous nociceptive stimulation (Roy et al, 1992;Villanueva et al, 1989). Thus, non-somatotopic, viscerocutaneous nociception in ACC derives from spinal cord, subnucleus reticularis dorsalis and parabrachial nuclei via the MITN.…”
Section: Source and Latency Of Visceral Nociceptive Signalmentioning
confidence: 99%
“…In this new context, it could be interesting to investigate whether noxious visceral inputs conveyed in the lemniscal system to the forebrain arise only from the dorsal column nuclei or from two neighbouring, parallel systems in the dorsal-most aspect of the caudal medulla, viz. the Cu and SRD, since SRD units are also driven by visceral noxious inputs (Roy et al, 1992).…”
Section: Projections From the Cu To The Diencephalon: Functional Consmentioning
confidence: 99%
“…By comparison with other brainstem reticular neurons (for reviews, see Bowsher, 1976;Gebhart, 1982;Villanueva et al, 1996), this population does not respond to visual, auditory or proprioceptive stimuli and encodes the intensity of noxious thermal, mechanical, and visceral stimuli Roy et al, 1992). The A␦-and C-fiber evoked activities of these neurons are depressed by morphine in a dose-related and naloxone-reversible fashion and the spinal pathways responsible for their activation ascend in the ventro-lateral funiculi (Bing et al, 1990).…”
mentioning
confidence: 98%